Experimental research on the thermal state of a shell for noise and heat insulation of the gte90l2 gas turbine engine used for the mechanical drive of the gcu-c-16s turbo-compressor package - Щербаков, Олег Миколайович; Ткаченко, Дмитро Олександрович; Парафійник, Володимир Петрович; Гуріненко, Володимир Михайлович; Костюк, Володимир Євгенович; Cкрипка, Олексій Іванович; Кирилаш, Олена Іванівна (Eastern-European Journal of Enterprise Technologies, 2015)
We have devised a methodology and obtained experimental findings on the thermal state of the noise and heat insulation shell in the GTE90L2 gas turbine engine designed by the State Enterprise Gas Turbine Research & Production Complex (SE GTRPC) Zorya-Mashproekt as a part of the turbine of the GCU-C-16S gas pumping units produced by the Sumy Machine Building Research and Production Association and operated as a part of the Dolyna (Valley) compressor station. We studied the sustainable mode of the unit with three modes of the shell ventilation to measure the flow rate of air supplied to the shell, air temperature at 23 points and the temperature of the inner surfaces of the walls at 14 points in the shell, as well as the air temperature outside the enclosure. In our measurements, we used the MS-13 cup anemometer and a multi-channel information-measuring system that included temperature measurement sensors based on the TCA-type thermoelectric converters and protected from the effects of infrared radiation, as well as the MPS-M measuring point selection switch and the digital thermometer Technoterm 9503. The research was predetermined by the inability of the previous research data on the thermal state of the covers of drive turbine engines to prove the adequacy of the mathematical model for the thermal state of standardized shells for noise and heat insulation of engines for gas pumping units designed by the Sumy Machine Building Research and Production Association. We have determined the thermal state of the noise and heat shell of the GTE90L2 gas turbine engine as a part of the GCU-C-16S gas pumping unit operated as a part of the Dolyna (Valley) compressor station. The research has revealed, in particular, uneven distribution of temperatures of the air and internal surfaces of the shell walls as well as a significant effect of heat radiation from the engine upon the thermal state of the shell. The obtained data on the thermal state of the shell are useful and important for producers of gas pumping equipment with gas turbine drives since their quality and quantity are sufficient for verifying the generalized mathematical model of the thermal state of shells, and the methods of their obtaining are free from the shortcomings that are inherent in the previous studies.